Entrepreunership Implementation As Moderation In The Success Of Small And Medium Entreprises (SMEs) - Humairoh, Humairoh; Annas, Mohammad (International Journal of Advanced Multidisciplinary, 2023)
This study aims to determine the implementation of entrepreneur and entrepreneurship on the success of SMEs businesses both partially and simultaneously and to determine the performance of entrepreneurship as a moderating variable between entrepreneurial variables on the success of SMEs businesses. This type of research is quantitative research. The sample in this study amounted to 92 respondents using a simple random sampling technique, namely respondents from SMEs in Tangerang City Mall. Data were taken using a questionnaire instrument with a Likert scale rating of 1-5 and analyzed using SPSS version 26 software. The results showed that partially there was a positive and significant influence of the entrepreneur variable on business success, entrepreneurship had a positive and significant effect on business success simultaneously entrepreneur and entrepreneurship has a positive impact on business success and the entrepreneurship variable is a moderating variable between entrepreneurial variables on business success. The ability of the entrepreneur and entrepreneurship variables explains business success by 60.6%, as indicated by the magnitude of R Square 0.606. In comparison, the remaining 39.40% is influenced by other factors not included in this research model. With the multiple linear regression equation, Y = 2.228 + 0.542X1+ 0.394 X2 + e.